Correction: cytoNet: Spatiotemporal network analysis of cell communities. - Arun S Mahadevan; Byron L Long; Chenyue W Hu; David T Ryan; Nicolas E Grandel; George L Britton; Marisol Bustos; Maria A Gonzalez Porras; Katerina Stojkova; Andrew Ligeralde; Hyeonwi Son; John Shannonhouse; et al. (PLoS Computational Biology)
[This corrects the article DOI: 10.1371/journal.pcbi.1009846.].